Seismic Stratigraphy and Marine Magnetics of the Naples Bay (Southern Tyrrhenian Sea, Italy): The Onset of New Technologies in Marine Data Acquisition, Processing and Interpretation - Aiello, Gemma; Giordano, Laura; Marsella, Ennio; Passaro, Salvatore (IntechOpen, 2012)
None